Studi Korelatif Pengalaman Guru Mengikuti Diklat terhadap Kemampuan Pengelolaan Kelas di MTs Negeri 1 Kebumen Tahun 2021 - Subarkah, Imam (Prodi Pendidikan Agama Islam IAINU Kebumen, 2022)
This research aims to: (1) find out the experience of MTs Negeri 1 teachers after attending training (2) find out the teacher's ability in classroom management at MTs Negeri 1 Kebumen (3) find out whether there is a correlation between teachers' experiences following training and classroom management abilities at MTs Negeri 1 Kebumen. This research is in the form of field research with quantitative methods. This research is a population study because there were only 40 respondents. The research was conducted at MTs Negeri 1 Kebumen. The population of this research was 40 MTs Negeri 1 Kebumen teachers. The data collection technique used the questionnaire method, the data analysis technique used correlation. The data analysis used is quantitative data analysis. The data analysis technique used is data presentation, product moment correlation analysis. Based on the research, it can be concluded that: (1) The experience of MTs Negeri 1 Kebumen teachers following training is in the good category. This can be seen from the analysis results which show a mean value of 25.82, namely in the interval 24-28. (2) Class management at MTs Negeri 1 Kebumen is included in the good category. This can be seen from the analysis results which show a mean value of 34.1, namely in the interval 32-37. (3) The results of this research show that there is a positive and significant correlation between teachers' training experience and classroom management skills at MTs Negeri 1 Kebumen, which is 0.429. Because the calculated r (rxy= 0.429) is greater than the rtable both at 5% significance and at the 1% significance level.